Multilingual English users’ linguistic innovation - Wei, Li (World Englishes, 2020)
Can ‘non‐native’ speakers of English innovate in English? This seemly simple question bothers sociolinguists and sociolinguistic research because we feel uncertain whether the ‘inventive’ productions by ‘non‐native’ speakers should be treated as evidence of creativity or mistakes. This article aims to tackle this question from a translanguaging perspective, using data from social media communication amongst multilingual English users in the Sinophone world. Examples include a range of creative expressions that mix elements of English with those from other languages and semiotic means. A translanguaging perspective raises questions about the very notion of named languages and offers a radically different way of analysing these expressions as socio‐politically meaningful linguistic innovations. The theoretical and methodological implications of the translanguaging approach for the study of linguistic innovation by multilingual language users and for the study of world Englishes are discussed.